1994
DOI: 10.1007/3-540-58715-2_143
|View full text |Cite
|
Sign up to set email alerts
|

Branching rules for satisfiability

Abstract: Recent experience suggests that branching algorithms are among the most attractive for solving propositional satis ability problems. A k ey factor in their success is the rule they use to decide on which v ariable to branch next. We attempt to explain and improve the performance of branching rules with an empirical model-building approach. One model is based on the rationale given for the Jeroslow-Wang rule, variations of which have performed well in recent w ork. The model is refuted by carefully designed com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 8 publications
0
27
0
Order By: Relevance
“…The selection of the branching literals is an important factor for the efficiency (Hooker and Vinay, 1995). Obviously, infeasible instances and instances with tight non-renewable resource constraints might consume a lot of CPU time using the activity list discussed previously, since this list does not contain guiding information to select variables to branch.…”
Section: Pre-processingmentioning
confidence: 99%
“…The selection of the branching literals is an important factor for the efficiency (Hooker and Vinay, 1995). Obviously, infeasible instances and instances with tight non-renewable resource constraints might consume a lot of CPU time using the activity list discussed previously, since this list does not contain guiding information to select variables to branch.…”
Section: Pre-processingmentioning
confidence: 99%
“…172-173). However, [19] has experimentally disproved their original justification and shown that the reason behind the success of JW heuristic is that it creates simpler sub-problems. This, in turn, leads to faster SAT solving.…”
Section: Literal Activity and Clause Lengthmentioning
confidence: 99%
“…Our SAT solution algorithm uses a clause-based search tree [13,10]. At every iteration, a clause C s to be satisfied is selected.…”
Section: Clause Hardness Evaluationmentioning
confidence: 99%
“…Priority is given to unit clauses (unit resolution). After them, since starting assignment by satisfying the more difficult clauses is known to be very helpful in reducing backtracks [10], we select hardest clauses. Hardness of a clause is evaluated by means of the below ϕ(C j ).…”
Section: Clause Hardness Evaluationmentioning
confidence: 99%